Optimal Layout of Chord Graph into the Windmill Graph - Shalini, M Arul Jeya; Abraham, Jessie; Aswathi, D (International Journal of Computer Sciences and Engineering, 2025)
Graph embedding is an important and extensively studied theory in parallel computing. A great deal of research has been devoted to finding “good” embedding of one network into another. The embedding of a guest graph G into a host graph H is defined by a pair of injective functions between them. The edge congestion of an embedding is the maximum number of edges of the guest graph that are embedded on any single edge of the host graph. The optimal layout problem deals with finding the embedding for which the sum of all the shortest paths in corresponding to the edges in is minimum. In this paper, we find the optimal layout of embedding the chord graph into the windmill graph